Catalytic Properties of Amylolytic Enzymes Produced by Gongronella butleri Using Agroindustrial Residues on Solid-State Fermentation. (10th December 2017) - Cavalheiro, Gabriéla Finoto; Sanguine, Isadora Stranieri; Santos, Flávia Regina da Silva; Costa, Ana Carolina da; Fernandes, Matheus; Paz, Marcelo Fossa da; Fonseca, Gustavo Graciano; Leite, Rodrigo Simões Ribeiro
Abstract : Amylases catalyze the hydrolysis of starch, a vegetable polysaccharide abundant in nature. These enzymes can be utilized in the production of syrups, alcohol, detergent, pharmaceutical products, and animal feed formulations. The aim of this study was to optimize the production of amylases by the filamentous fungus Gongronella butleri by solid-state fermentation and to evaluate the catalytic properties of the obtained enzymatic extract. The highest amylase production, 63.25 U g −1 (or 6.32 U mL −1 ), was obtained by culturing the fungus in wheat bran with 55% of initial moisture, cultivated for 96 h at 25°C. The enzyme presented optimum activity at pH 5.0 and 55°C. The amylase produced was stable in a wide pH range (3.5–9.5) and maintained its catalytic activity for 1 h at 40°C. Furthermore, the enzymatic extract hydrolyzed starches from different vegetable sources, presenting predominant dextrinizing activity for all substrates evaluated. However, the presence of glucose was observed in a higher concentration during hydrolysis of corn starch, indicating the synergistic action of endo- and exoamylases, which enables the application of this enzymatic extract to produce syrups from different starch sources.